Cytotoxic Effect of Ethanolic Extract of Sarang Semut (Myrmecodia pendens) on HeLa Cervix Cancer Cell Line In Vitro Experimental Study - Fatmawati, Dina; Puspitasari, Prista Karina; Yusuf, Iwang (Fakultas Kedokteran; Universitas Islam Sultan Agung (UNISSULA), 2011)
Background: Sarang semut (Myrmecodia pendens) is a traditional plant that has been known to contain anti cancer components. Flavonoids and tannins were contained in sarang semut plant which are believed has cytotoxic effect against cancer cell line. This study aims at cytotoxic effect ethanolic extract of sarang semut at various concentrations on HeLa cervical cancer cell line.Design and Method: The method was quasi experimental with post test only non equivalent control group design. HeLa cell was divided into two groups. The first group as positive control with doxorubicin, second group as treatment with ethanolic extract of sarang semut at various concentrations. Ethanolic extract of sarang semut concentrations used were 3,91 Î¼g/ml; 7,81 Î¼g/ml; 15,63 Î¼g/ml; 31,25 Î¼g/ml; 62,50 Î¼g/ml; 125 Î¼g/ml; 250 Î¼g/ml; 500 Î¼g/ml; 1000 Î¼g/ml. Cytotoxic effect was evaluated by direct counting method with tryphan blue dye then using probit regression analysis to find IC50 value.Result: Inhibitory concentration 50 (IC50) value ethanol extract of sarang semut was 33,28 Î¼g/ml. Ethanol extract of sarang semut had a cytotoxicity effect categorized as the moderately active (20 Ã¬g/ml< IC50< 100Ã¬g/ ml). Inhibitory concentration 50 (IC50) value doxorubicin was 5,56 Î¼g/ml. Cytotoxicity effect of doxorubisin higher than cytotoxicity effect of ethanolic extract of sarang semut.Conclusion: Ethanolic extract of sarang semut (Myrmecodia pendens) had a cytotoxic effect categorized as the moderately active on HeLa cell (Sains Medika, 3(2):112-120).